Isolation, Characterization, and In Vitro Differentiation of Mesenchymal Stem Cells from Human Umbilical Cord into Islet-Like Clusters - Kanafi, Mohammad Mahboob; Doavi, Tahereh (Regeneration, Reconstruction & Restoration (Triple R), 2017)
Introduction: Mesenchymal stem cells (MSCs) are easy to isolate, culture, and manipulate in ex-vivo culture. MSCs were identified in several other organs such as umbilical cord which is focused in present project. Type 1 Diabetes mellitus is caused due to e damage of the pancreatic beta cells resulting in absolute insulin insufficiency. Transplantation of insulin-producing islet cells could be considered as an effective therapy for type 1 diabetes. Materials and Methods: In this project we aimed to enzymatically isolate stem cells from human umbilical cord. The mesenchymal properties of these isolated cells were checked by flow cytometry technique. Their differentiation potentials were further studied, particularly with respect to islet like clusters (ILCs) which were generated through a three steps induction protocol. The amount of secreted insulin has been measured using insulin ELISA kit. Results: Stem cells were successfully isolated from human umbilical cord. Cells expressed high level of mesenchymal markers and they had both osteogenenic and adipogenic differentiation potential. Through a 10 days of islet induction, most of the obtained islet like aggregates were positive for DTZ, a zinc-chelating agent known to selectively stain pancreatic β-cells. They were also able to secrete insulin. Conclusion: MSCs isolated from the human umbilical could be differentiated into ILCs that possess the ability to produce insulin. Therefore human umbilical cord blood-derived MSCs (hUCMSCs) seem to be an excellent source of stem cells that can be used in the therapeutic procedures for type 1 diabetes.